2003
DOI: 10.1007/978-3-7091-0643-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of Parkinson’s disease in rodents induced by toxins: an update

Abstract: Summary. The development of animal models of Parkinson's disease is of great importance in order to test substitutive or neuroprotective strategies for Parkinson's disease. Such models should reproduce the main characteristics of the disease, such as a selective lesion of dopaminergic neurons that evolves over time and the presence of neuronal inclusions known as Lewy bodies. Optimally, such models should also reproduce the lesion of non-dopaminergic neurons observed in a great majority of patients with Parkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 71 publications
1
53
0
Order By: Relevance
“…ϩ is a metabolic product of MPTP and is known to induce cell death in dopaminergic neurons (1,3). To demonstrate the specific role of TRPC1, we transformed SH-SY5Y cells with either antisense TRPC1 constructs or overexpressed TRPC1 using adenoviral constructs.…”
Section: Trpc1 Protects Sh-sy5y Cells Against Mpp ϩ -Induced Cell Toxmentioning
confidence: 99%
See 2 more Smart Citations
“…ϩ is a metabolic product of MPTP and is known to induce cell death in dopaminergic neurons (1,3). To demonstrate the specific role of TRPC1, we transformed SH-SY5Y cells with either antisense TRPC1 constructs or overexpressed TRPC1 using adenoviral constructs.…”
Section: Trpc1 Protects Sh-sy5y Cells Against Mpp ϩ -Induced Cell Toxmentioning
confidence: 99%
“…Parkinson's disease is a progressive neurodegenerative disorder associated with selective loss of the dopaminergic neurons in the substantia nigra pars compacta (1). Neurotoxins, such as 1-methyl-4-phenylpyridinium ion (MPP ϩ ), 1 cause selective nigral dopaminergic lesions and cause Parkinsonian syndrome (2)(3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated oxidative stress as the major initiator of apoptotic cell death in several neurodegenerative disorders, including PD (Zigmond et al, 2002;Dawson and Dawson, 2003;Di Monte, 2003;Jenner, 2003;Kanthasamy et al, 2003;Thiruchelvam et al, 2003;Greenamyre and Hastings, 2004;Maguire-Zeiss et al, 2005;Przedborski and Ischiropoulos, 2005;McCormack et al, 2006). The potent dopaminergic toxin MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydro--pyridine) causes an irreversible PD-like syndrome in humans, non-human primates, and in animals, and reproduces most of the neurochemical and pathological hallmarks, including the substantial degeneration of dopaminergic neurons; consequently, MPTP has been used extensively in experimental PD models (Dauer and Przedborski, 2003;Hirsch et al, 2003b;Przedborski et al, 2004;Bove et al, 2005;Smeyne and Jackson-Lewis, 2005;Watanabe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although the cause of AD progression is unclear, AD is characterized by inflammatory responses to amyloid-β (Aβ), microglia activation, and astrocyte recruitment by Aβ deposits [7]. Parkinson's disease (PD) is occurs by loss of dopaminergic neurons in the substantia nigra (SN) and by many other events and agents, such as, genetic events or toxic drugs or chemicals, such as, 1-methyl-4-phenyl-1,2,3-6 tetrahydropyridine or rotenone [8,9]. Pathologic changes in the PD brain are closely related to microglial activation induced inflammation, which accelerates dopamine (DA)-producing neuron death.…”
Section: Relations Between Microglial Activation and Neuronal Cell Dementioning
confidence: 99%